Liberals, Marxists, and Nationalists. Competing interpretations of South African History: A Rejoinder to a Rejoinder (Historia, 2021)
In the course of her eight-page rejoinder [Historia, May 2009] to the five reviews of her book [Historia, November 2008], Merle Lipton writes of my "aggressive attack" on her book. It is always difficult to know whether or not to respond to such a rejoinder. Will one, in so doing, give a book that does not deserve much attention even more attention? On the other hand, not to reply will leave Lipton with the last word and readers unclear about how the reviewers would respond to what she says. For this reason I have decided that I should briefly address some of the inaccurate and misleading assertions that she makes about what I had said in my review.